Efecto del Tratamiento Alcalino (NaOH) en la Digestibilidad de la Materia Seca y Proteína de la Totora (Scirpus californicus) en Cuyes (Cavia porcellus) - Castro Bedriñana, Jorge Isaac (2017)
The study aimed to evaluate the effect of alkaline treatment of the California bulrush (Scirpus californicus) treated with sodium hydroxide (NaOH) at 2, 3 and 4% on a dry basis, on dry matter and protein digestibility in guinea pigs (Cavia porcellus). The digestibility tests were conducted on 16 adult male guinea pigs of the Inti genetic line. Four animals were used per treatment: (T1): California bulrush without alkaline treatment, (T2) with 2% NaOH, (T3) with 3% NaOH, and (T4) with 4% NaOH. The digestibility coefficients of dry matter in T1 to T4 were 63.46, 65.27, 69.88 and 70.86% respectively, where T1 and T2 were significantly different from T3 and T4 (p<0.01). In the case of total protein, the digestibility values were 73.86, 75.06, 78.46 y 81.25% respectively, where T3 and T4 were greater and different between each other (p<0.01). It is concluded that the treatment of California bulrush with NaOH was effective in improving the digestibility of dry matter and crude protein, especially at the level of 4% NaOH.